Anaerobic Digestion 2019
DOI: 10.5772/intechopen.80815
|View full text |Cite
|
Sign up to set email alerts
|

Review of Mathematical Models for the Anaerobic Digestion Process

Abstract: To describe anaerobic fermentation, many mathematical models have been suggested. A commonly accepted hypothesis in microbial growth is the speed of cellular reproduction, which is proportional to the concentration of cells at that instant. The constant of proportionality between the speed of growth and cell concentration is called cell growth rate, μ. In many occasions, the cell growth rate is considered constant. This leads to conclude that the concentration of cells versus time presents an exponential funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 39 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…The kinetic of methane production in a reactor can be conveniently represented by a modified Gompertz function (Díaz et al, 2011; Velázquez‐Martí et al, 2018). Following Lay et al (1997) a modified three‐parameter Gompertz equation (Equation 1) was applied in this study to describe the dynamic of CH 4 production.M)(t=MtruemaxexpexpeRtruemaxMtruemaxλt+1,where M (t) (ml CH 4 ‐STP g −1 VS) is the cumulative amount of CH 4 produced, in standard conditions for temperature and pressure (STP); t (days) is the elapsed time; M max (ml CH 4 g −1 VS) is the maximum cumulative CH 4 production; e (exp) is the Euler's number; R max (ml CH 4 day −1 g −1 VS) is the maximum CH 4 daily production rate; and λ is the lag time duration (days), that is the time of microbial adaptation before exponential CH 4 production begins.…”
Section: Methodsmentioning
confidence: 99%
“…The kinetic of methane production in a reactor can be conveniently represented by a modified Gompertz function (Díaz et al, 2011; Velázquez‐Martí et al, 2018). Following Lay et al (1997) a modified three‐parameter Gompertz equation (Equation 1) was applied in this study to describe the dynamic of CH 4 production.M)(t=MtruemaxexpexpeRtruemaxMtruemaxλt+1,where M (t) (ml CH 4 ‐STP g −1 VS) is the cumulative amount of CH 4 produced, in standard conditions for temperature and pressure (STP); t (days) is the elapsed time; M max (ml CH 4 g −1 VS) is the maximum cumulative CH 4 production; e (exp) is the Euler's number; R max (ml CH 4 day −1 g −1 VS) is the maximum CH 4 daily production rate; and λ is the lag time duration (days), that is the time of microbial adaptation before exponential CH 4 production begins.…”
Section: Methodsmentioning
confidence: 99%
“…In general, the VS concentration of animal manure from the analyzed data is not so high, which means that the average ranges for the production of pretreated methane from cow, pig and poultry manure are 238, 271 and 328 mL/g VS, respectively. According to Velázquez et al [110], substrates with low, medium and high methane production are characterized by having productions between 150 and 300 mL/g VS, between 300 and 400 mL/g VS, and more than 450 mL/g VS, respectively. In this research, the average methane production of cow and pig manure corresponds to a low production, while the methane production of poultry corresponds to an average production.…”
Section: Effect Of Pretreatments On Cow Pig and Poultry Manurementioning
confidence: 99%
“…Finally, the methane productions generated by camelids correspond to a medium‐high range according to the literature. Velázquez et al 100 . reported that methane productions of 150–300, 300–450, more than 450 mL CH 4 /g VS corresponds to a low, medium, and high classification respectively.…”
Section: Discussionmentioning
confidence: 99%